Determination of thrusts to generate artificial equilibrium points in binary systems with applications to a planar solar sail - de Almeida, A. K.; Prado, A. F.B.A.; Yokoyama, T. [UNESP] (Springer Nature, 2019)
In this work, the artificial equilibrium points for a general two-body system are derived, visualized, and summarized as functions of the direction of the thrust, for several directions. The results for the Sun-Earth system are also presented. Planar solar sail applications are also considered.
Keywords: Artificial equilibrium point; Astrodynamics; Nonlinear systems; Restricted three-body problem; Solar sail